Explaining Governance Failure in Islamic Microfinance Institutions: Integrating Risk Governance and Maqasid al-Shariah - M Sholeh Wafie; Slamet Slamet; Khusnudin Khusnudin; Moch Mahsun (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: The sustainability of Islamic Microfinance Institutions (IMFIs) is threatened by a lack of governance. Previous research has addressed issues of financial performance and regulatory compliance largely at the expense of governance dynamics, organizational resilience, and Islamic ethical values. This research attempts to analyze governance failure by applying Risk Governance Theory, Shariah Governance, and Maqasid al-Shariah and aims to construct a Maqasid-Based Risk Governance Model. Methods: A qualitative multiple-case study design was conducted on BMT Global Insani and BMT Mitra Umat. Data collection consisted of semi-structured interviews, collection of internal documents, regulatory reports, and other supporting documents. Reflexive thematic analysis with methodological triangulation was used to analyze the data. Results: Two pathways of governance failure were identified: structural governance failure and governance erosion. Both pathways lead to the deterioration of organizational resilience. Evaluating the state of governance revealed poor governance integrity, ineffective participatory risk identification, insufficient adaptive risk mitigation, and deteriorating ethical leadership. To address these issues, a Maqasid-Based Risk Governance Model is proposed which combines the above elements and governance effectiveness. Conclusion and Suggestion: Governance failure in Islamic Microfinance Institutions transcends the domains of leadership, organizational culture, and accountability, and adaptive governance capability. The model addresses the gap in governance scholarship by incorporating Maqasid al-Shariah as the primary strategic governance concern and providing tailored recommendations for Islamic Microfinance Institutions, governance regulators, and Shariah Supervisory Boards. It is suggested that the model be quantitatively tested in multiple governance contexts.